Undergraduation in Advertising: history, concepts and teaching trajectory (Research, Society and Development, 2021)
The teaching of undergraduation in Social Communication, with a minor on Advertising, emerged in the second half of the 20th century from demands established mainly by the media market. In this context, we reflected on the history, the concept and the paths of Advertising in Brazil, as well as its trajectory in Higher Education, in order to understand training in this area. From this contextualization, this paper aims to study and understand the dynamics involving the constitution of Advertising in the country, and how this process (has) generated reflections on the teaching and training of students in this area. The study was carried out through bibliographical and documentary research, from a qualitative approach. Among the main discussions undertaken is the reflection on the separation – still present – between the theoretical and practical dimensions in Communication and how this division is directly related to training in Advertising. All these issues have implications on teaching, whose directions end up following predominantly market paths, often even instrumental, due to all the historical, financial and cultural relationship with the market.